The Improvement of Productivity to Increase Company Competitiveness in PT. X Binjai - Kodrat, Kimberly Febrina (PT Mattawang Mediatama Solution, 2022)
Productivity is a measurement of the ability for an input in resulting of an output. The productivity for a company is an important element that can create the effectiveness, efficiency, and quality for its operational activities. This research is aimed to design a developmental system of productivity and improvement of productivity which can be applied by the company in increasing the competitiveness. Its methodology used is explanatory research. The productivity is made by measuring data of manpower, material, energy, and capital. The model of productivity improvement is using employee base technique. The research shows that the productivity index of manpower, material, energy and capital is fluctuated. In running the activity of productivity process, there is still inefficiency in distributing the manpower, material, energy, and capital for the company